Methoxychlor and Vinclozolin Induce Rapid Changes in Intercellular and Intracellular Signaling in Liver Progenitor Cells - Babica, Pavel; Zurabian, Rimma; Kumar, Esha R; Chopra, Rajus; Mianecki, Maxwell J; Park, Joon-Suk; Jaša, Libor; Trosko, James E; Upham, Brad L (Toxicological sciences, 2016)
Methoxychlor (MXC) and vinclozolin (VIN) are well-recognized endocrine disrupting chemicals known to alter epigenetic regulations and transgenerational inheritance; however, non-endocrine disruption endpoints are also important. Thus, we determined the effects of MXC and VIN on the dysregulation of gap junctional intercellular communication (GJIC) and activation of mitogen-activated protein kinases (MAPKs) in WB-F344 rat liver epithelial cells. Both chemicals induced a rapid dysregulation of GJIC at non-cytotoxic doses, with 30 min EC50 values for GJIC inhibition being 10 µM for MXC and 126 µM for VIN. MXC inhibited GJIC for at least 24 h, while VIN effects were transient and GJIC recovered after 4 h. VIN induced rapid hyperphosphorylation and internalization of gap junction protein connexin43, and both chemicals also activated MAPK ERK1/2 and p38. Effects on GJIC were not prevented by MEK1/2 inhibitor, but by an inhibitor of phosphatidylcholine-specific phospholipase C (PC-PLC), resveratrol, and in the case of VIN, also, by a p38 inhibitor. Estrogen (ER) and androgen receptor (AR) modulators (estradiol, ICI 182,780, HPTE, testosterone, flutamide, VIN M2) did not attenuate MXC or VIN effects on GJIC. Our data also indicate that the effects were elicited by the parental compounds of MXC and VIN. Our study provides new evidence that MXC and VIN dysregulate GJIC via mechanisms involving rapid activation of PC-PLC occurring independently of ER- or AR-dependent genomic signaling. Such alterations of rapid intercellular and intracellular signaling events involved in regulations of gene expression, tissue development, function and homeostasis, could also contribute to transgenerational epigenetic effects of endocrine disruptors.
Keywords: androgenní receptory; receptory pro estrogeny; potkani inbrední F344; Receptors, Estrogen; Cell Line; mitogenem aktivované proteinkinasy p38; Cell Communication; signální transdukce; insekticidy; Gap Junctions; Methoxychlor; Signal Transduction; MAP kinasový signální systém; methoxychlor; krysa rodu Rattus; MAP Kinase Signaling System; Stem Cells; Animals; mitogen-activated protein kinases; játra; p38 Mitogen-Activated Protein Kinases; non-genomic signaling.; phosphatidylcholine-specific phospholipase C; zvířata; mezerový spoj; Rats; epigenetic toxicity; Insecticides; buněčné linie; konexin 43; Connexin 43; Rats, Inbred F344; Liver; Oxazoles; oxazoly; endocrine disruptors; gap junctional intercellular communication; Receptors, Androgen; kmenové buňky; mezibuněčná komunikace